Crystal structure of 5,6-diphenyldibenzo[c, g]chrysene, C38H24 - Bin Zhang (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C38H24, monoclinic, C2/c (no. 15), a = 37.6829(14) Å, b = 7.4695(3) Å, c = 17.4881(7) Å, β = 95.269(3)°, V = 4901.6(3) Å3, Z = 8, Rgt(F) = 0.0472, wRref(F2) = 0.1177, T = 123(2) K.